EMPLOYEE RETENTION AND TURNOVER USINGMOTIVATIONAL VARIABLES AT INDIA - Thirupathy, A.; Dhayalan, C. (International Journal of Research -GRANTHAALAYAH, 2016)
This research looked at the extent to which identified intrinsic and extrinsic motivational variables influenced the retention and reduction of employee turnover in both public and private sector organizations. The research was aimed at achieving the following objectives: identify and establish the key intrinsic and extrinsic motivational variables being used by selected public and private sector organizations in retaining their employees; determine the extent to which the identified intrinsic and extrinsic motivational variables are influencing employees’ retention and turnover in the selected organizations; and make recommendations to management of the selected organizations on how to effectively retain employees and reduce turnover. The study adopted the cross-sectional survey research design, investigating the extent to which selected motivational variables influence employees’ decision to either remain or quit an organization. Quantitative research design was used and this design was chosen because its findings are generalizable and the data objective. The study examined two public and two private sector organizations in India. The total population of the research comprised 1800 employees of the surveyed organizations with a sample size of 145 respondents. A self-developed questionnaire, measured on a Likert Scale was used to collect data from respondents. The questionnaire had a Cornbrash alpha coefficient of α = 0.85 suggesting that the instrument was reliable. The Chi-square test of association was used in testing the hypothesis of the study. The result showed that employees in both public and private sector organizations were, to a very large extent, influenced to stay in their respective organizations by a combination of intrinsic and extrinsic motivational factors. The following motivational variables were found to have significantly influenced employee retention in both the public and private sector organizations: training and development, challenging/interesting work, freedom for innovative thinking, and job security.